THE SPORT PSYCHOLOGY MODEL FOR LONG TERM ATHLETE DEVELOPMENT - Singhnoy, Chatkamon (Journal of Education and Innovation, 2024)
The purpose of this article is to present a sports psychology model for long-term athlete development, which integrates mental skill development into a systematic training program. The model consists of three stages: 1) Fundamentally, sports psychology involves fostering fundamental psychological skills and adaptability of the mind. The overarching objective is to initially cultivate essential mental proficiencies, encompassing self-awareness, mental frameworks, intrinsic motivation, and goal establishment. 2) In the preparatory phase of sports psychology, the focus lies on mental groundwork facilitated by skill enhancement. This facet of sports psychology incorporates various techniques such as constructive self-dialogue, effective pre-game rituals, visualization, as well as sustained concentration. And 3) competitive sports psychology addresses the sustenance of self-assurance and constructive thought patterns. The implementation of this model is suitable for coaches and sports psychologists. It is also beneficial for parents and athletes who can work together to design training programs tailored to the specific mental needs of each phase. This collaborative approach is essential for achieving sporting goals and is critical to future success as a systematic approach to improving the mental game and developing athletic performance.